Detection of antimicrobial activity of aqueous and alcoholic extracts of Lepidum sativum seeds - Hassan M. Resen; Jameel M.Badi; Mustafa M.Abd Al razak; Raheem H. Resen (Journal of Madenat Alelem University College, 2018)
The study was carried out to detect the sensitivity of various bacteria (Escherichia coli،Proteus vulgaris، Klebsiella pneumonae ، Shigella sp ، Salmonella typhi) against different concentrations ( 8,12,17 mg/0.1 ml) of Lepidum sativum seeds extracts (aqueous ,ethanolic and methanolic ). The results obtained were cleared that all the extracts have shown a wide range of antibacterial effects against applied bacteria.  This sensitivity include all the concentrations used specially against  Escherichia coli and Salmonella typhi and this sensitivity increased with the increasing of the extract concentration. Finally, best results which were given a high inhibition effect for the aqueous extract among other extracts when 17 mg/ 0.1 ml  used.The obtained results included the detection of many functional groups (Glycosides, Flavonoids, Alkaloids, Tannins, Proteins, Steroids and Phenols) which had been done by different chemical reagents proceeded according to methods mention in the published articles.